Risk assessment and management handbook for environmental, health, and safety professionals - Kolluru, Rao V (McGraw-Hill, 1996)
As environmental risks increase, and potential liabilities mount, it is essential to assess the risk of a process before starting. This handbook provides a guide to all types of risk assessments that need to be performed in business and industry.